2004
DOI: 10.1091/mbc.e04-08-0673
|View full text |Cite
|
Sign up to set email alerts
|

Cleavages within the Prodomain Direct Intracellular Trafficking and Degradation of Mature Bone Morphogenetic Protein-4

Abstract: Pro bone morphogenetic protein-4 (BMP-4) is initially cleaved at a consensus furin motif adjacent to the mature ligand domain (the S1 site), and this allows for subsequent cleavage at an upstream motif (the S2 site). Previous studies have shown that S2 cleavage regulates the activity and signaling range of mature BMP-4, but the mechanism by which this occurs is unknown. Here, we show that the pro-and mature domains of BMP-4 remain noncovalently associated after S1 cleavage, generating a complex that is targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
125
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 60 publications
10
125
1
1
Order By: Relevance
“…Alternatively, the secondary structure of Xlefty, or the inherent protease sensitivity at each site, may differ between oocytes and embryonic tissues, such that CS2 cleavage does not occur in embryonic tissues. A general conclusion from our studies, therefore, despite the numerous reported experiments using Xenopus oocytes to infer the mechanisms regulating the biochemical processing of secreted proproteins (Dale et al, 1989;Thomsen and Melton, 1993;Jones et al, 1996;Cui et al, 1998Cui et al, , 2001Eimon and Harland, 2002;Degnin et al, 2004), is that only embryonic cells should be used for future studies of Xlefty.…”
Section: Cleavage Of Xlefty Is Required To Block Xnr Signaling But Nomentioning
confidence: 74%
See 3 more Smart Citations
“…Alternatively, the secondary structure of Xlefty, or the inherent protease sensitivity at each site, may differ between oocytes and embryonic tissues, such that CS2 cleavage does not occur in embryonic tissues. A general conclusion from our studies, therefore, despite the numerous reported experiments using Xenopus oocytes to infer the mechanisms regulating the biochemical processing of secreted proproteins (Dale et al, 1989;Thomsen and Melton, 1993;Jones et al, 1996;Cui et al, 1998Cui et al, , 2001Eimon and Harland, 2002;Degnin et al, 2004), is that only embryonic cells should be used for future studies of Xlefty.…”
Section: Cleavage Of Xlefty Is Required To Block Xnr Signaling But Nomentioning
confidence: 74%
“…Cleavage at site 1 (S1) separates the ligand from the prodomain and subsequent cleavage within the prodomain (at S2) seems to be required in order to disrupt non-covalent prodomain/ligand interactions, which releases the BMP-4 ligand for productive receptor engagement (Cui et al, 2001). When the BMP-4 ligand remained prodomain-associated, the complex seems to be targeted for efficient degradation via the lysosomal/proteosomal pathway (Degnin et al, 2004). Therefore, Degnin et al (2004) suggested that tissue-specific cleavage at S2 might contribute to the spatiotemporal regulation of BMP-4 activity.…”
Section: Cleavage Of Xlefty Is Required To Block Xnr Signaling But Nomentioning
confidence: 99%
See 2 more Smart Citations
“…1A) (15). The BMP4 ligand forms a transient, noncovalent complex with the prodomain following cleavage at the S1 site, but subsequent cleavage at the S2 site disrupts the complex, freeing the ligand from the prodomain (20).…”
Section: Significancementioning
confidence: 99%